Taṭbīq Namūżaj al-Ta’līm al-Ta’āwuni litarqiyyah Mahārah al-Qirā’ah li Ṭullāb al-Madrasah al-Mutawassiṭah - Mukaromah, Muhimmatul; Amperawati, Revita Intan Nur (Study Program of Arabic Language Teaching, 2024)
This study aims to determine the effectiveness of the Cooperative Think Pair Share Model on Reading Ability in Understanding Arabic reading texts in Eighth Grade Students of MTs Ma'arif Balong Ponorogo. The method used in this study is a quantitative approach of the experimental model with a quasi-experimental research type. The sample in this study consisted of 28 students in the experimental class and 26 students in the control class. Data collection in this study used test techniques, observation, and interviewing techniques. The data analysis used is the Independent Sample t-test and N-Gain test. The results showed that (1) There is a difference in reading ability in understanding reading texts between using the think pair share learning model (experimental class) and not using the think pair share learning model (control class) in the Arabic language subject. This is evidenced by using an independent sample t-test, which results in less than 0.05, meaning Ho is rejected and Ha is accepted. (2) there is effectiveness in improving reading ability in understanding Arabic Reading texts, as evidenced by the N-Gain score of 67.9%, which is categorized as quite effective, so it can be concluded that the cooperative learning model think pair share is effectively used for the Eighth Grade students of MTs Ma'arif Balong Ponorogo.